Partisipasi Masyarakat dalam Membangun Desa Mandiri di Desa Wayau Kecamatan Tanjung Kabupaten Tabalong - Efendy, Noor; Arbain, Taufik; Riduansyah Syafari, Muhammad (Journal of Comprehensive Science, 2025)
The problem that arises in this study is that people only want to participate if there is a reward from the Government. This study uses a qualitative descriptive research method. The results of the study in decision-making still have minor obstacles in building and directing community participation in attending the Musrenbangdes meeting. Participation in the implementation in addition to active community participation, the role of the government is also very much needed to direct, guide, supervise, and provide a budget as a form of government concern for rural development. The Village Head and his staff are quite active and have succeeded in carrying out their functions and roles so that they have been quite successful in completing one of the basic infrastructures of their village. This development activity involves the community in mutual cooperation to build infrastructure facilities that have gone well. The utilization of the development produced at this time has provided sufficient benefits for the interests and needs of the community. Community participation in evaluating development results is quite good. Suggestions to the Head of Wayau Village to improve the professionalism of the Village Apparatus.